Roasting's Effects on Proximate and Amino Acid Content of Maize - Ejoh, Nonso; Onyeulo, C.G. (Talenta Publisher, 2022)
The main objective of this research is to compare the amino acid and proximate compositions of raw and roasted maize samples. Complete randomized experimental design with triplicates replications was applied. From the analysis, we were able to obtain the following values: total carbohydrates (78.28-79.85 percent), crude protein (7.32-7.05 percent), crude fat (2.70-2.20 percent), crude fiber (2.40-2.10 percent) and ash (2.10-2.50 percent) for both raw and roasted maize seeds. Prolonged exposure to the heat from roasting altered the amino acid content as obtained from the result. The concentration of amino acids in the seeds was reduced by the heat effect. The highest concentration of leucine was contained in seeds, with a value of 1.30 g/16 g N and 0.95 g/16 g N in the case of the raw and roasted seeds, respectively. Lysine and tryptophan concentrations were low, but they contain equal quantities of amino acids containing sulphur, which are methionine and cystine.